Pengaruh Modal Usaha Dan Ketersediaan Tenaga Kerja Terhadap Keberhasilan Usaha - Waruwu, Desy Paquita; Siregar, Yamin (Universitas Medan Area, 2024)
This article aims to analyze the influence of business capital and labor availability on the success of the Doorsmeer Mobil Goods Auto Medan business. This type of research is associative research with a quantitative approach. The research population was 32 entrepreneurs and employees at the Goods Auto Medan car doormeer and the sample was determined using total sampling, namely the entire population became the research sample. Data collection techniques include distributing questionnaires to obtain primary data and documentation to obtain secondary data. The statistical data analysis technique used is multiple linear regression and previously classical assumptions were tested such as heteroscedasticity, normality, multicollinearity. Coefficient of determination testing and hypothesis testing were also carried out. The results of the study showed the conclusion that there is a partial influence of business capital (qp value q0.001 qq0.05) and labor availability (pvalue qq0.05) on the success of the doorsmeer business Goods Auto Medan cars. Simultaneously there is an influence of business capital and labor availability qp value q0.000 q q0.05 on the success of the Goods Auto Medan car doorsmear business.